ADVANTAGES OF THE G/XPERT XDR METHOD IN ACCURATE DIAGNOSIS OF DRUG-RESISTANT TUBERCULOSIS - Massavirov Sherali Sherikbaevich; Ghaffarov Bakhodir Khojakbarovich (European Science Publishing, 2025)
For medicines drug-resistant tuberculosis (DR-TB) globally health in storage the most serious from problems one to be, in particular, many to medicines resistant (MDR-TB) and wide to medicines resistant (XDR-TB) forms treatment makes it difficult. In this article GeneXpert MTB/XDR method to medicines durable tuberculosis exactly diagnostic advantages scientific based in case deep analysis is done. Method to rifampicin endurance detected in patients isonazid, fluoroquinolones, the second-row injection drugs and to ethionamide endurance from 90 minutes less time inside high sensitivity (93–96 %) and to oneself with specificity (98–99 %) to find out takes. In the article of the method speed is high accuracy, as a reflex test application, economic efficiency and low and middle profitable in countries current verb ease separately is emphasized. Thus together, less numerical mutations passing sent situations and additional for tests need like limitations also seeing will be released. Summary as to say possible, GeneXpert MTB/XDR in modern tuberculosis control revolutionary weapon is, WHO until 2035 tuberculosis no to do to the strategy important contribution adds.
Keywords: To medicines drug-resistant tuberculosis, XDR-TB, GeneXpert MTB/XDR, molecular diagnostics, fluoroquinolone resistance, isonazid endurance, fast diagnosis, WHO recommendations, antibiotic resistance.